Migration of BTEX and Biodegradation in Shallow Underground Water through Fuel Leak Simulation. (1st November 2016) - Cheng, Yaping; Chen, Yudao; Jiang, Yaping; Jiang, Lingzhi; Sun, Liqun; Li, Liuyue; Huang, Junyu
Abstract : To provide more reasonable references for remedying underground water, fuel leak was simulated by establishing an experimental model of a porous-aquifer sand tank with the same size as that of the actual tank and by monitoring the underground water. In the tank, traditional gasoline and ethyl alcohol gasoline were poured. This study was conducted to achieve better understanding of the migration and distribution of benzene, toluene, ethyl benzene, and xylene (BTEX), which are major pollutants in the underground water. Experimental results showed that, compared with conventional gasoline, the content peak of BTEX in the mixture of ethyl alcohol gasoline appeared later; BTEX migrated along the water flow direction horizontally and presented different pollution halos; BTEX also exhibited the highest content level at 45 cm depth; however, its content declined at the 30 and 15 cm depths vertically because of the vertical dispersion effect; the rise of underground water level increased the BTEX content, and the attenuation of BTEX content in underground water was related to the biodegradation in the sand tank, which mainly included biodegradation with oxygen, nitrate, and sulfate.